2017
DOI: 10.1021/acs.jced.6b00976
|View full text |Cite
|
Sign up to set email alerts
|

Liquid–Liquid Equilibria for the Extraction of Chloropropanols from 1,2-Dichloropropane Using Water or 1,4-Butylene Glycol

Abstract: Liquid−liquid equilibria (LLE) data for the extraction of chloropropanols from 1,2-dichloropropane using water or 1,4-butylene glycol as solvent at 303.15 and 323.15 K under atmospheric pressure have been determined. The distribution coefficients and separation factors were calculated to assess the effectiveness of extracting chloropropanols from 1,2-dichloropropane, and the consistency of LLE data was verified by the Othmer−Tobias and Hand equations. The binary interaction parameters among these compounds wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Additionally, the GUM standard 25 was utilized to determine the uncertainty of the mass compositions for the two enriched phases, which has been used elsewhere. 26,27 The estimated uncertainty of the equilibrium mixture (in mass fraction) was <0.0050.…”
Section: Experimental Designmentioning
confidence: 95%
“…Additionally, the GUM standard 25 was utilized to determine the uncertainty of the mass compositions for the two enriched phases, which has been used elsewhere. 26,27 The estimated uncertainty of the equilibrium mixture (in mass fraction) was <0.0050.…”
Section: Experimental Designmentioning
confidence: 95%
“…The LLE data was measured from 298.15 to 323.15 K and the standard uncertainty was ±0.1 K, and then the mixtures were used to fill the 50 mL glass-sealed equilibrium cell before being agitated vigorously for more than 2 h with the magnetic stirrer . The mixtures were allowed to settle for more than 6 h to ensure sufficient phase separation and equilibration and were separated into organic and aqueous phases (Some preliminary experiments have been done, and these indicated that this period was sufficient to allow complete phase separation and keep the system in thermodynamic equilibrium.) 1,4-Dioxane was utilized as an internal standard to obtain the calibration factor, and the internal standard method was applied to determine the composition of the sample.…”
Section: Methodsmentioning
confidence: 99%
“…Calculating the objective function (OF) can obtain the regression interaction parameters of the above thermodynamic model. as described below. , where w cal and w exp refer to the calculated and experimental composition of components; subscripts k , j , and i denote the tie-line, phase, and components respectively; M refers to the quantity of tie lines.…”
Section: Resultsmentioning
confidence: 99%